PENGARUH LINGKUNGAN KERJA DAN MOTIVASI KERJA TERHADAP KEPUASAN KERJA PEGAWAI PUSDATIN KEMENTERIAN ENERGI SUMBER DAYA MINERAL - Sari, Ratih Permata; Lestari, Nurlaela Eva Puji (Jurnal Ekonomika dan Manajemen, 2024)
This research aims to determine how much influence the work environment and work motivation have on employee job satisfaction, which includes the independent variables (independent) that the environment and work motivation have an influence on the dependent variable. The population in this study was all employees, totaling 67 employees. Data processing was carried out in this research using SPSS version 26. Data sampling obtained through questionnaires was tested for quantity, namely validity, reliability and hypothesis testing using multiple linear regression, T test and F test, determination (R2). The results of multiple linear regression show that job satisfaction is influenced by the work environment by 2.744, work motivation by 0.513. This shows that the work environment with a t value of 7.314 > t table 1.997 and a significant value of 0.00 < 0.05 partially has a significant effect on job satisfaction, work motivation a t value of 8.236 < t table 1.997 and a significant value of 0.00 < 0.05 partially has a significant effect on employee job satisfaction. The results of the coefficient of determination (R2) use an r square value of 0.859. This is proven by the work environment and work motivation showing fcount 176.092 > ftable 3.140. With a significant value of 0.00 < 0.05, it simultaneously has a significant effect on employee job satisfaction at the Ministry of Energy and Mineral Resources' Data and Data Center.